Metode Dakwah Pondok Pesantren Al-Aqsa Dalam Pembinaan Akhlaq Remaja - Anisah, Anisah (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2013)
This study aims to determine the form of preaching in the moral guidance of adolescents, identify preaching techniques, preaching approach strategies, and the results achieved from the preaching methods used by the Al-Aqsha Modern Islamic Boarding School. This study uses a descriptive. This study uses Lasswell's mass communication theory as a theoretical framework to analyze the da'wah process from the message source (da'i), message (morals), channel (Al-Aqsha Modern Islamic Boarding School), message recipient (adolescents), to the effect in the form of behavioral change. The results of this study are expected to contribute to the development of methods for fostering youth morals based on Islamic boarding schools and serve as a reference for other da'wah institutions.